Study on cow's milk protein allergy and specific foods for allergic (Research, Society and Development, 2022)
Cow's milk protein allergy (CMPA) is an inflammatory condition against some proteins present in cow's milk and is the most common food allergy in children. The objective was to evaluate infant formulas recommended for CMPA and develop specific and informative material about the studied subject. The work was done in two stages: (1) investigation of infant formulas for infants with CMPA in supermarkets and drugstores in the city, and (2) creation of educational material. A total of 30 formulas was found, 24 of them repeated, among the 13 investigated places, that was composed of six different formulas for evaluation, in three categories: hydrolyzed formulas, soy protein-based formulas, and free amino acid-based formulas. Infant formulas intended for infants with APLV have a higher marketing value than conventional infant formulas. Most of the formulas had nutrients according to the evaluated resolutions. The free amino acid formula was found in less variety and higher price. The educational material created brought information about what CMPA is, differences in symptoms, information about treatment, infant formulas for infants with CMPA, foods that should be excluded and which should be included, and five recipes that would originally contain milk. Overall, the study showed a good result in appropriate nutrients and labeling of special formulas. The booklet was prepared in a didactic way, easy to access and that brings the information of great help for parents or people with CMPA.